The coin of the realm [videorecording (DVD)] : Spokane House 1810-1826 (s.n.], 2008)
The Coin of the Realm presents the story of the fur trade at Spokane House during the period of 1810 to 1826. The scenes depict the everyday life of the trappers, traders and their families. The demand for beaver fur to be used in making felt hats brought Europeans to the Spokane area and led to the establishment of Spokane House.